JUAL BELI SISTEM ONLINE DI ERA DIGITAL MENURUT HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Isnu Harjo Payitno; Andi Sulasmi; Tarno Tarno; Encep Saefudin; Rahmat Dadang (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of the implementation of Community Service entitled "Buying and Selling Online Systems According to the View of Islamic Law and Positive Law" is as an effort to fulfill the obligations of the Three Principles of Higher Education as mandated in Article 1 paragraph 9, Law No. 12 of 2012 concerning Higher Education. Based on the foregoing, Community Service (PKM) activities in the form of providing knowledge and understanding of the Online Sale and Purchase of Systems. The method used in this Community Service is in the form of counseling on the understanding of the Concept of Buying and Selling Online System accompanied by the view of Islamic Law (Sharia) and Positive Law which covers both Criminal, Civil and existing Regulations. The Community Service Result obtained is a basic understanding and desire of PKM objects to be able to know the signs and anticipate the negative effects of evil behavior.Keywords: Dedication, Buying and Selling Online, Islamic Law, Positive Law